Bioconservation Management of Protected Forest Areas: A Case Study in the West Rinjani Forest Management Unit: Pengelolaan Biokonservasi Kawasan Hutan Lindung: Studi Kasus di Unit Pengelolaan Hutan Rinjani Barat - Anugrah, Raden Dendy; Manzis, Haeki; Cahyani, Inda Nur; Arini, Fitri Sandya (Indonesian Journal of Tropical Biology, 2025)
Sustainable forest management is essential to maintaining ecological integrity and improving community welfare. This study aims to assess the performance of the West Rinjani Forest Management Unit (KPHL Rinjani Barat) in implementing conservation-based forest governance. A descriptive qualitative approach was applied, involving field observations, semi-structured interviews with key stakeholders, and document analysis. The data were analyzed using the Miles and Huberman interactive model through data reduction, data display, and conclusion drawing. The results indicate that KPHL Rinjani Barat achieved the highest performance score (3) across all six evaluation indicators, including competency standards, operational consistency, planning effectiveness, and implementation of forest utilization and protection. Despite this, only 20% of the long-term forest management plan (RPHJP) could be executed due to limited financial support. The study concludes that while institutional performance is strong in planning and community facilitation, funding constraints hinder full implementation. This highlights the urgent need for policy reform in budgeting systems to strengthen forest governance at the local level. Scientifically, this study supports the integration of bio-conservation principles into decentralized forest management and recommends increased state and stakeholder investment to ensure ecological sustainability and socio-economic benefits for forest-dependent communities.